دراسة إمكانية إنتاج سماد عضوي من مخلفات أحطاب القطن - بوعيسى عبد العزيز; سمرة بديع; يوسف علي (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة في الفترة 2006-2008 في كلية الزراعة جامعة تشرين بهدف الحصول على سماد عضوي من مخلفات أحطاب القطن وذلك من خلال تخميرها بإضافة مصدر آزوتي (62.5)غ آزوت على شكل يوريا ومصدر للفوسفور (64,4)غ P2O5على شكل سوبر فوسفات لكل 20 كغ من المخلفات والمحافظة على رطوبة بحدود (55-60%) لمدة ستة أشهر، وتمت مراقبة تغيرات بعض الخصائص الفيزيائية والكيميائية لأحطاب القطن خلال فترة التخمير بأخذ عينات دورية وتحليلها مخبريا. ازدادت الكثافة الظاهرية للمخلفات أثناء تخميرها بنسبة 60% في نهاية التجربة ووصلت درجة الـPH في المادة المخمرة إلى 6.7 وانخفضت النسبةC/N من 1/69 إلى 1/18 وازدادت الناقلية الكهربائية وكذلك المحتوى من العناصر المعدنية. This study was carried out in the Faculty of Agriculture at Tishreen University during the period 2006-2008 to obtain organic manure from cotton stalk residues by 6-month fermentation involving the addition of (62.5 g) N as Urea manure, (64.5 g) P2O5 as Superphosphate manure per 20 Kg of cotton stalk residues, and keeping moisture between (55 and 60 %). During fermentation, we studied the changing of some physical and chemical characters of organic matter by analyzing the samples bi-monthly. Bulk density increased by 60 %,: PH value of the fermented materials reached 6.7; the rate of C/N reduced from 69/1 to 18/1, whereas EC and the content of mineral elements increased.